PERAN PENDIDIK SEBAGAI ROLE MODEL PENDIDIKAN SEKS USIA REMAJA DALAM PERSPEKTIF ISLAM DI SMK AL-GHOZALY SIWATU BUMIROSO WATUMALANG WONOSOBO TAHUN PELAJARAN 2021/2022 - Khusnul Khotimah; Samsul Munir; Lutfan Muntaqo (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2021)
This research is about the role carried out by educators on adolescent sex education in an Islamic perspective at SMK Al-Ghozaly Siwatu Bumiroso Watumalang Wonosobo, with the formulation of the problem: (1) What is the concept of sex education at SMK Al-Ghozaly? , (2) How is the Implementation of adolescent sex in SMK Al-Ghozaly?, (3) What is the Role of Educators as role models of sex education at SMK Al-Ghozaly? This research uses a qualitative, descriptive approach conducted at SMK Al-Ghozaly using a case study design. The data collection methods used include: observation methods, interview methods, and documentation methods. Informants are selected using a series of processes of data collection, reduction, presentation and verification of data as well as analysis in case (within analysis). The credibility of the data will be checked by checking the adequacy of the reference. Meanwhile, dependability and confirmability are achieved through auditing by supervisors. The results showed that: The concept of sex education at SMK Al-Ghozaly is a real effort to provide understanding to every student about knowledge about sex appropriately and in the presence of Allah SWT. So that noble morals or customs will be embedded in every aspect of life and the implementation of sex education at SMK Al-Ghozaly is presented in an integrated manner into the subject of Islamic Religious Education, and educators also agree to insert lessons on sex education at every opportunity. In addition to schools presenting sex education through integrated materials in Islamic Religious Education learning, they also support through special activities, namely studies that are carried out every two weeks on Thursdays after Dhuhur. In addition, the school also entered into a cooperation agreement with the Watumalang sub-district health office, which in this case is a puskesmas and also cooperates with the pesantren to provide the study of the book of fiqh, such as the recitation of the book of safinatun naja, Risalatul mahidh, I'anatun nisa', 'Uqud al-lijain, Qurrotul 'Uyun. The role of educators towards sex education at SMK Al-Ghozaly is that teachers as teachers, teachers as mentors, teachers as mediators, and teachers as evaluators.